Organization Of Tourist Awareness Groups In The Development Of Bedengan Tourism Park In Kaliasri Village, Kalipare District, Malang Regency - Widyasari, Anisya Yulis; Zulkarnain, Zulkarnain; Rahma, Rezka Arina (Universitas Negeri Malang, 2024)
Community organization is a group of individuals who come together to create a program or activity aimed at bringing about change in their community. When a community is capable of taking action towards positive change, it is considered empowered. This is evident in the case of the community in Kaliasri Village, which has recognized its local potential and managed to turn it into a tourism attraction. To manage this tourism effort, the community of Kaliasri Village established a group known as the